SYNTHESIS OF 7-SUBSTITUTED 3-beta-D-RIBOFURANOSYL-3H-IMIDAZO[2,1-i]PURINES - Karskela T; Klika KD; Lonnberg H (INST ORGANIC CHEM AND BIOCHEM, 2022)
A method for the synthesis of 7-substituted 3-beta-D-ribofuranosyl-3H-imidazo[2,1-i]purines has been devised whereby compounds were prepared in a few steps from a common intermediate, 3-(2',3'-O-isopropylidene-beta-D-ribofuranosyl)-3H-imidazo[2,1-i]purine-7-carbaldehyde, obtained from the reaction of 2',3'-O-isopropylideneadenosine with bromomalonaldehyde. The formyl group of the carbaldehyde was subsequently reductively aminated and the resulting secondary amines were then further derivatized either by acylation, lactamization or reductive alkylation.